Predictors of emerging reading skills in Turkish:|Evidence from Kurdish-Turkish bilingual early readers - Öz, Mahsume. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
In Turkey, Kurdish is one of the most spoken languages after Turkish; however, there is not enough knowledge regarding Kurdish-Turkish successive bilingual children’s literacy development. Hence, the current study explored the role of component processes, phonological awareness (PA), phonological memory (PM), rapid automatized naming (RAN), and vocabulary, in predicting real word reading (WRD) and pseud-word reading (PWD) abilities of Kurdish-Turkish bilingual students learning to read in Turkish. Adopting a cross-sectional research design, it investigated the relationships between reading-related components and reading outcomes by referring to the differences between grade levels. Besides, the role of linguistic and cognitive factors in contributing to word-level reading performance was explored through multiple and hierarchical regression analyses across grades. Participants were 81 Kurdish-Turkish bilingual children attending Grade 1 and Grade 2. They were tested on a battery of literacy measures in Turkish. The results indicated that second graders significantly performed better at all of the tasks compared to first graders with the exception of vocabulary. According to regression analyses, PA emerged as the strongest predictor of dependent measures assessing word reading ability at Grade 1. PM and RAN were found to be significant contributors to WRD abilities at Grade 2. Taken together, the findings of the study have shown that as the grade level increased, PA tended to lose its strength whereas PM and RAN gained more importance in predicting word reading success.
Keywords: Kurdish language -- Turkey.; Turkish language -- Vocabulary.; Reading Skills Competency Tests.